THE INFLUENCE OF TAX AVOIDANCE, CURRENT TAX EXPENSE, AND DEFERRED TAX EXPENSE ON EARNINGS MANAGEMENT - Dinanti, Dara; Nuryati, Tutty; Yulaeli, Tri; Nurbaiti, Beti; Ningrum, Endah Prawesti (Cahaya Ilmu Bangsa, 2025)
Previous research or relevant research is very important in a scientific research or article. Previous research or relevant research serves to strengthen theories and phenomena of relationships or influences between variables. This article reviews the effects of tax avoidance, currentcurrent tax and deferred tax expense on profit management. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in future research. The results of this literature review article are: 1) Tax avoidance affects earning management; 2) Current tax affects earning management; 3) Deferred tax expense affects earning management.